A justiça e a produção do Direito em Castela no século XV - Vidotte, Adriana [UNESP] (Pontifícia Universidade Católica do Rio Grande do Sul (PUC-RS), 2011)
The Catholic kings government - Fernando of Aragon and Isabel of Castille - (1474-1504) is set in Middle to Modern Age transition period and was considered a period of justice and peace in Castille. It makes us possible to question about implications, to law, of a kingdom organization in a transition era. We propose to verify what characterize the passage from a medieval law to a modern law, and which elements indicate this transition in catholic kings government. We emphasize two main prerrogatives, a medieval tradition, a judge one, and another of modern character, the legislative, that close on Fernando and label tradition.
Justice and Law production in Castille in Century XV
Keywords: Justice; Law; Monarchy